Analysis Of Style Language On The Speech Text Of National Speech Contest Winner The Japan Foundation - Endang Puji Astuti; Yuniarsih; Eky Kusuma Hapsari (Kagami : Jurnal Pendidikan dan Bahasa Jepang, 2021)
The purpose of this study is to determine the style of language rhetorical form of alliteration, hyperbole, and rhetorical questions. Furthermore, the style of figurative language in the form of simile, metaphor, metonimia, and personification that also observed in the text of the manuscript of the speech contained on the winner from the first and the second winner of the National Japanese Speech Contest The Japan Foundation in 2018-2019. This research apply qualitative descriptive analysis method: the author collects the data using documentation technique. Afterwards, the basic techniques (immediate constituents technique) from agih method is applied to to analyze the data. The finding of the study shows there are 22 data, on the style of the language of rhetorical; zero alliteration, one hyperboles, and 10 rhetorical questions. Then on the style of figurative language there are three similes, six metaphors, zero metonimia, and two personifications. The style of language that most used is rhetorical questions. A rhetorical question is intended to reinforce the words to be conveyed as well as the provoke technique of conversation by forcing the listener to join as well as thinking to solve the problem.